UPAYA GURU PAI DALAM PENGANGGULANGAN GAYA HIDUP HEDONISME MELALUI PEMBELAJARAN PAI DI SMAN 9 SIJUNJUNG - Emilza Tri Murni (Sekolah Tinggi Ilmu Tarbiyah (STIIT) Ahlussunnah Bukittinggi, 2018)
The lifestyle of hedonism is a lifestyle whose main purpose is theenjoyment of the world for a moment. The majority of adolescents at this timeare lifestyle hedonism and lifestyle hedonism one of the culture that plunge onjuvenile delinquency. One effort to overcome the lifestyle of hedonism inschool is through learning PAI. Ledger hedonism of learners belonging tohedonism that includes wearing uniforms not inserted, wearing coloredshoes, long hair for male students, smoking in school, hanging out in stallswhen lessons. The work done by PAI teachers to overcome the hedonismlifestyle is by directly rebuking, giving reinforcement at the beginning oflearning, controlling program, dhuha prayer program and praying dzuhurjama'ah, the program of reciting the Qur'an before the learning starts. Intackling the hedonism lifestyle of teachers PAI faced many obstacles that HRstudents at SMAN 9 Sijunjung is still very low and religious knowledge is stilllacking so they are easily influenced and participate in the lifestyle ofhedonism.